Mechanistic insights into the sol-gel synthesis of complex (quaternary) Co–Mn–Zn-spinel ferrites: An annealing dependent study. Issue 11 (1st August 2020) - Bhandare, Shilpa V.; Kumar, R.; Anupama, A.V.; Choudhary, H.K.; Jali, V.M.; Sahoo, B.
Abstract: Synthesis conditions, cation distribution at tetrahedral and octahedral sites and their stability play very important roles in controlling phase-purity and physicochemical properties of spinel ferrite compounds. In this work, an attempt is made to understand how the progress of phase-formation and the structural and magnetic properties are influenced by the annealing temperature and nature of cations used in the synthesis of quaternary spinel ferrite ceramics. A series of Co0.8-x Mn0.2 Znx Fe2 O4 (x = 0, 0.2, 0.4, 0.6 and 0.8) (CMZF) spinel ferrite samples were synthesized by citric acid assisted sol-gel technique followed by annealing at 400, 600 and 800 °C. To compare the progress of phase formation/stability of the cations, simple (binary) spinel ferrite reference samples, such as CoFe2 O4, MnFe2 O4 and ZnFe2 O4, were also synthesized by the same technique and are calcined at the same conditions. In case of CoFe2 O4, all the samples have single phase spinel structure, but a transformation from an inverse spinel-type to nearly normal spinel ferrite-type cation distribution is observed with increasing annealing temperature. The as-prepared MnFe2 O4 sample and that annealed at 400 °C show formation of single phase spinel ferrite, while those annealed at 600 and 800 °C decomposes completely into Mn2 O3, α-Fe2 O3 and amorphous-FeO phases. In contrast, for ZnFe2 O4 samples, a transformation from the ZnO and α-Fe2 O3 phases (present in the as-prepared and up to 600 °C annealed samples) to pure ZnFe2 O4 –phase occurs only at/above 800 °C. Interestingly, our results show that the progress of the phase formation behavior of the CMZF samples can be predominantly considered as a combination of the behavior and energetics typically exhibited by the individual (simple) ferrite systems. Overall, our work provides the necessary impetus for achieving the phase purity and required physicochemical properties of complex ferrite systems by choosing the cations suitably, based on their nature and annealing behavior.